Analysis of Marginal Group Political Participation at Banyuwangi Regency Election 2020: Study in Transvestite and Gay Communities: Analisis Partisipasi Politik Kelompok Marginal pada PILKADA Kabupaten Banyuwangi 2020: Studi pada Komunitas Waria dan Gay - Erna Agustina; Niko Pahlevi Hentika (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
This research raises issues of political participation of marginalized groups (transvestites and gays) in regional head elections in Banyuwangi Regency in 2020. Seeing the number of transvestites and gays in Banyuwangi Regency which reached 979 people. If viewed from the number of votes, of course, they surely can influence the election results in Banyuwangi Regency. Transvestites and gays are very interesting to study, because they have high exclusivity and different ways of socializing in society in general and of course have unique political interests and expectations of public policies that benefit them. The results showed that, although transvestite and gay groups have a distinctive pattern compared to other groups of society, especially those related to their political interests. However, the political participation of gay and transvestite groups belongs to the observer group. That is, gay and transvestite groups only participate in voting in the vote only